The Moderating Role of Meaning of Work in The Relationship Between GHRM and Organizational Commitment - Ika Wahyu Kurniawati; Dorojatun Prihandono; Taufiq Hidayat (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2026)
This study aims to examine the influence of Green Human Resources Management (GHRM) and Meaning of Work (MoW) on Organisational Commitment (OC), while also testing the moderating role of MoW in the relationship between GHRM and OC. The research was conducted on employees from various organizational sectors in Semarang, Indonesia, involving 111 respondents selected through purposive sampling. Data were collected via an online questionnaire and analyzed using multiple regression and moderation analysis techniques. The findings reveal that GHRM does not have a direct significant effect on organisational commitment. In contrast, MoW has a significant positive effect on OC and serves as a moderator that strengthens the relationship between GHRM and OC. This indicates that the effectiveness of green HR practices in enhancing employee commitment largely depends on the employees’ perception of meaningful work. The study provides practical insights for HR practitioners to align environmental strategies with employees’ personal values and sense of purpose. By doing so, organizations can build stronger affective commitment among employees, especially in urban-industrial contexts like Semarang. The study contributes to the development of sustainable HR strategies by emphasizing the psychological factors that influence employees' responses to environmental policies.